Morphological and Molecular Identification of Anisakis spp. (Nematoda: Anisakidae) in Commercial Fish from the Canary Islands Coast (Spain): Epidemiological Data - Natalia Martin-Carrillo; Katherine García-Livia; Edgar Baz-González; Néstor Abreu-Acosta; Roberto Dorta-Guerra; Basilio Valladares; Pilar Foronda (Animals, 2022)
The study aimed to perform the molecular identification of Anisakis larvae in commercial fish from the coast of the Canary Islands and to provide data on their infection level for the host and the species of this nematode parasite that we could find in several species of commercial interest in the Canary Archipelago. Fish specimens (n = 172) from the Canary coasts were examined for parasites. In total, 495 larvae were identified; PCR was carried out for the entire ITS rDNA and cox2 mtDNA region, obtaining sixteen sequences for the entire ITS rDNA region and fifteen for the cox2 mtDNA, this being the first contribution of nucleotide sequences of Anisakis species of fish caught from the Canary Islands. An overall prevalence of 25% was obtained in the fish analyzed, and five species of Anisakis were identified, these being Anisakis simplex (s.s.), Anisakis pegreffii, Anisakis physeteris, Anisakis nascettii and Anisakis typica and the hybrid Anisakis simplex x Anisakis pegreffii. The results obtained in this study have relevance for public health, since the pathology will depend on the species of Anisakis, so it is important to know the health status of fish in the waters of the Canary Islands to assure a safer consumption and take adequate measures, in addition to the provision of epidemiological data.